Assessment of the economic evaluation of the contrast agent Iomeron in percutaneous coronary intervention - A. S. Kolbin; I. A. Vilum (Izdatelstvo OKI, 2018)
Percutaneous coronary intervention (PCI - angiography and stent placement) aren't possible without X-ray contrast agents. Contrast enhancement depends on the iodine concentration, while the safety of particular contrast agents diff ers. Th e aim of the study is to conduct health economic evaluation of Iomeron (Bracco Imaging S.p.A., Italy) in patients with acute coronary artery disease treating with PCI. Th e cost-eff ectiveness analysis, cost-minimization analysis, sensitivity analysis and budget impact analysis were used. In results, we can say that Iomeron is cost-eff ective comparing to iodixanol, iohexol, iopromide and ioversol.